2021
DOI: 10.3389/fpls.2021.651015
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Metabolism Is Induced in Common Bean During Early Seedling Development

Abstract: Nucleoside hydrolases (NSH; nucleosidases) catalyze the cleavage of nucleosides into ribose and free nucleobases. These enzymes have been postulated as key elements controlling the ratio between nucleotide salvage and degradation. Moreover, they play a pivotal role in ureidic legumes by providing the substrate for the synthesis of ureides. Furthermore, nucleotide metabolism has a crucial role during germination and early seedling development, since the developing seedlings require high amount of nucleotide sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“… 45 In the process of seed germination, the involvement of purine metabolism in the myriad of bioenergetic processes is required for the mobilization of storage products; moreover, active nucleotide biosynthesis is needed to provide sufficient pyrimidine nucleotides to the embryos to facilitate nucleic acid synthesis. 46 In this study, we observed that some nucleotides (cytosine, CAMP, cytidine, deoxyadenosine and guanosine) involved in the purine metabolism pathway accumulated significantly during the germination of Z. Nitidum seed, consistent with the varying trend of nucleotides during seed germination of common beans, 47 castor, 48 Arabidopsis thaliana 49 and other seeds. This finding indicates that a large number of nucleotides are required for the germination of Z. nitidum seeds in addition to the mobilization of nutrients in cotyledons.…”
Section: Discussionsupporting
confidence: 77%
“… 45 In the process of seed germination, the involvement of purine metabolism in the myriad of bioenergetic processes is required for the mobilization of storage products; moreover, active nucleotide biosynthesis is needed to provide sufficient pyrimidine nucleotides to the embryos to facilitate nucleic acid synthesis. 46 In this study, we observed that some nucleotides (cytosine, CAMP, cytidine, deoxyadenosine and guanosine) involved in the purine metabolism pathway accumulated significantly during the germination of Z. Nitidum seed, consistent with the varying trend of nucleotides during seed germination of common beans, 47 castor, 48 Arabidopsis thaliana 49 and other seeds. This finding indicates that a large number of nucleotides are required for the germination of Z. nitidum seeds in addition to the mobilization of nutrients in cotyledons.…”
Section: Discussionsupporting
confidence: 77%
“…Nucleosides have been identified as root-secreted compounds in exudates of a few plant species (Strehmel et al, 2014;Tawaraya et al, 2014;Warren, 2015;Tang et al, 2022). However, recent works, using metabolomic approach, discovered that nucleoside secretion from roots is a common phenomenon of plants (McLaughlin et al, 2023) and that profound changes in their contents occur during plant development (Delgado-Garcıá et al, 2021). Nucleosides are mainly utilized as nutrients when other carbon sources such as sugars and amino acids are exhausted.…”
Section: Introductionmentioning
confidence: 99%
“…The search for chemoreceptor ligand binding domains by Pfam 31.0 and UniProt reference proteome databases revealed only one putative nucleoside binding domain, the gate domain model, and only few nucleotides binding domains (Ortega et al, 2017). Being building blocks of nucleic acids, nucleoside secretion is energetically and nutritionally demanding especially in early development of plants (Delgado-Garcıá et al, 2021), implying that they may act as signaling molecules rather than as nutrients. Consequently, we hypothesized that root-secreted nucleosides serve as signaling molecules that play a key role in the assemblage and configuration of the rhizosphere microbiome.…”
Section: Introductionmentioning
confidence: 99%